Program Rumah Les Sebagai Upaya Peningkatan Pengetahuan Akademik dan Keterampilan Non Akademik Anak-Anak Di Desa Jompie - Irwan, Irwan; Ja'faruddin, Ja'faruddin; Arsyad, Nurdin; Nyulle, Rusdianto; Utary, Utary (Jurusan Matematika FMIPA UNM, 2025)
The progress of a nation depends on the quality of its human resources. One of the efforts to improve and develop the quality of human resources (HR) is quality education. Education is a very important tool for human survival. One of the problems that has become a major issue is the lack of equitable distribution of education. Therefore, in response to various obstacles in the implementation of education in Indonesia, students in Real Work Lecture (KKN) activities as a form of community service create a work program with the theme of tutoring houses. The method of implementation in this tutoring house program uses a direct approach method, namely conducting learning outside of school hours. The teaching method used is by using a game system. The tutoring program has a very important role in helping the children of Jompie Village achieve academic success and overcome learning difficulties. the tutoring program can be an effective tool in helping students achieve their academic potential. This is important in preparing them for a successful and fulfilling future.